Крик волка: [роман] / Андрей Дышев - Дышев Андрей Михайлович (Серия "Черная кошка", 1995)
Экземпляры: ф.4 (20210429) / Инвентарный номер: 61646 / Цена: 10.00 / Авт.знак: Д 91 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6